Implementasi Pembelajaran PKn Sebagai Pendidikan Karakter dI MI - Intan Dewi Mawardini (ASANKA : Journal of Social Science and Education, 2022)
ABSTRACTsiklus alamiah dalam tahap evolusi budaya suatu masyarakat seiring dengan perubahan In general, the purpose of education is to form one’s character. Character building sosial dan hadirnya modernitas; (2) Kecimol merupakan anti-tesa dari Gendang Beleq is one of the efforts to improve national development. In line with this, character sebagai bentuk perlawanan kelompok jajar karang terhadap Kelompok Purwangse yangdisebabkan oleh problem ekonomi-politik (ongkos) kebudayaan. development must always contain positive values. Within the scope of National Education, Citizenship Education is used as a forum to realize the goals of National Education. Character education should be given as early as possible. Starting from the Kata kunci: Gendang Beleq; Kecimol; Evolusi budaya; Pertentangan Kelasfamily and then assisted by educators in formal educational institutions starting fromthe basic education level. Success in character education in SD/MI can have an effect until he grows up because at that time children begin to be able to recognize good and bad things, with good guidance, students will be able to behave well and the quality of their education will increase and develop